Polymer Derived Ceramics with β‐Eucryptite Fillers: Filler‐Matrix Interactions1 . Issue 6 (24th March 2017) - Fedorova, Anna; Betke, Ulf; Scheffler, Michael
Abstract : Polymer derived ceramics with ß‐eucryptite are manufactured and filler‐matrix interactions in the temperature range between 800 and 1 100 °C are investigated. Pyrolysis temperatures above 1 000 °C led to changes of the β‐eucryptite phase, due to a significant SiO2 amount in the polymer derived ceramic matrix. A new phase, β‐spodumene, is formed; this is, confirmed by calculations of the lattice parameters. Scanning electron microscopy and energy dispersive x‐ray spectroscopy of the microstructure allow to localize spots on the matrix‐filler interface, where the described processes appear. Abstract : The phase composition and microstructure of Si–O–C/β‐eucryptite composites exhibiting a zero‐expansion behavior is evaluated using p‐XRD and SEM‐EDX. The β‐eucryptite filler consumes silica from the Si–O–C matrix above 1 000 °C and finally transforms into a new β‐spodumene phase.